Monocyte mimics improve mesenchymal stem cell-derived extracellular vesicle homing in a mouse MI/RI model. (October 2020) - Zhang, Ning; Song, Yanan; Huang, Zheyong; Chen, Jing; Tan, Haipeng; Yang, Hongbo; Fan, Mengkang; Li, Qiyu; Wang, Qiaozi; Gao, Jinfeng; Pang, Zhiqing; Qian, Juying; et al.
Abstract: Stem cell-derived extracellular vesicles (EVs) have been demonstrated to be effective in heart repair and regeneration post infarction. However, the poor homing efficiency and low yields of these therapeutics remain the major obstacles before they can be used in the clinic. To improve the delivery efficiency of EVs to ischemia-injured myocardium, we modified mesenchymal stem cell (MSC)-derived EVs with monocyte mimics through the method of membrane fusion. Monocyte mimic-bioinspired MSC-EVs (Mon-Exos) exhibited enhanced targeting efficiency to injured myocardium by mimicking the recruitment feature of monocytes after MI/RI, thus contributing to these exclusive adhesive molecules on monocyte mimics, particularly the Mac1/LFA1-ICAM-1 interaction. Through this strategy, Mon-Exos were shown to promote endothelial maturation during angiogenesis and modulate macrophage subpopulations after MI/RI, consistent with MSC-Exos biofunctions, and eventually improve therapeutic outcomes in cardiac function and pathohistology changes after treatments in a mouse MI/RI model. Ultimately, this strategy might provide us with a better way to assess the effects of stem cell EVs and offer additional techniques to help clinicians better manage regenerative therapeutics for ischemic heart diseases.